PENGARUH MODEL PEMBELAJARAN PJ4CS BERBANTUAN MEDIA CANVA TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA - Muh.Amin, Astuti (Universitas Cokroaminoto Palopo, 2025)
The selection of appropriate learning strategies and models is important to strengthen students' creative thinking skills. Based on the initial learning outcomes at SMA Negeri 5 Kota Ternate, it is known that the level of students' creative thinking is still low. They also have difficulty in developing creative thinking skills in biology learning. The purpose of the study was to identify the effect of the Pj4CS model on the creative thinking skills of class XI IPA students at SMA Negeri 5 Kota Ternate, North Maluku. The type of research used was a quasi-experimental, Non-Equivalent Control Group Design research design. The instrument used was a valid and reliable creative thinking ability instrument. The results showed that there was an effect of the Pj4CS model on the creative thinking skills of class XI IPA students at SMA Negeri 5 Kota Ternate. The syntax/stages of the Pj4CS learning model (Integrated Project-Based and 4C-Scaffolding) consisting of five stages including critical reading, communication for project determination, collaborative participation, scaffolding, and exploration of creativity have proven effective in improving students' creative thinking skills.